Who Reads E-Books? An Analysis Of Key Factors In E-Book Reading In The U.S. - Gu, Xin; Berger, Paul D. (Advances in Social Sciences Research Journal, 2018)
With the rapid increase in the number of e-book readers, researchers have become more and more interested in the factors that impact digital reading, because these factors are not only useful for marketing segmentation, but also important for optimizing marketing campaigns of an e-reader device company and the entire digital-publishing industry. In this paper, we perform stepwise linear regressions and independent sample t-tests (for differences in means) to determine the key factors in e-book reading behavior, and analyze how these factors affect e-book reading.